Ottoman Ulema, Turkish Republic: Agents of Change and Guardians of Tradition By Amit Bein (Stanford, CA: Stanford University Press, 2011. 224 pages.) (American Journal of Islam and Society, 2013)
Much has been written about religion and secularism in Turkey over the pastdecades, but detailed histories of the late Ottoman and modern Turkish ulemahave been few and far between. Therefore, this recent book by Amit Bein isa welcome and a much needed contribution to the literature on the Turkishulema and to the literature on religion in modern Turkey in general. It chartsthe vicissitudes of the ulema during a period of dramatic change from the latenineteenth century until roughly 1960. Bein shows the multiple challengesthe ulema faced during successive rounds of political and social reform andthe various approaches that they took in response. The diversity of opinionand political orientation within the ulema corps are on full display – from themost ardent nationalist figures, who supported state reforms in all respects, tothe staunchest enemies of the republican regime. This book conveys a nuancedunderstanding of who the Turkish ulema were and how they navigated theempire-to-republic transition ...